Obstacles and Solutions in Implementing Active Learning Strategies in Geography Learning Materials at SMA Negeri 11 Medan - Friska Salsabilla; Serli Sabela; Samadiana Br Sembiring; Risdo Hotray Sinaga (Sean Institute, 2024)
This research aims to identify obstacles and solutions in implementing active learning strategies in geography subjects at SMA Negeri 11 Medan. The research results show that the main obstacles faced consist of limited teacher competence, low student participation, limited time, and less than optimal use of existing facilities. Although facilities such as classrooms, projectors and computer laboratories are available, the use of traditional media such as globes and maps is increasingly rare. The proposed solutions include intensive training for teachers, use of digital technology, connecting material with students' daily lives, as well as an appreciation-based approach to increase student motivation. It is hoped that this research can contribute to the development of more effective and meaningful active learning, as well as improving the quality of education, especially in geography subjects .